Transcriptome sequencing and SSR prediction of Clematis calyx based on SMRT sequencing platform - Song Liu; Wei Song; Wei Pan; Gangshan Wu (Scientific Reports)
Abstract Clematis is an excellent vertical greening plant for garden viewing vines, with great ornamental and high medicinal value. To obtain transcriptome information and functional gene data for the Clematis calyx, this study utilized three biological replicates of the calyx from each of the three Clematis varieties: ‘Henryi’, ‘Polish spirit’, and ‘Mme Julia Correvon’ Single-molecule real-time sequencing technology was employed for full-length transcriptome sequencing. The study revealed that 21,673,173 non-chimeric sequences were identified through full-length transcriptome sequencing. After clustering, correction, and redundancy removal, 40,465 high-quality, full-length transcripts were obtained. Among these transcripts, there were 15,488 long non-coding RNA (lncRNA), 9,212 simple sequence repeats (SSR) sites, 1,247 transcription factors (TFs), 1,228 alternative splicing events, and 7,189 selectively polyadenylation sites predicted. In addition, 7,442 primer pairs were designed based on the SSR sites, covering 80.76% of the total SSR. 15 primer pairs were randomly selected for amplification, and 73.3% of them were successfully amplified. Transcript annotation results showed that 38,439, 38,094, 26,815, and 33,407 transcripts were annotated to the Nr, KEGG, KOG, and SwissProt databases, respectively. Among these, the KEGG database identified 137 metabolic pathways, including biosynthesis of secondary metabolites, carbon metabolism, and amino acid biosynthesis. 104 and 7 transcripts are involved in the flavonoid and anthocyanin metabolism pathways, respectively. The above results provide initial insights into the transcriptome information and functional characteristics of Clematis calyx. This critical data supports future research on marker primers for the color mechanism of Clematis calyx, the pathways and regulatory mechanisms of flavonoids and other products, as well as specific trait genes.